2019
DOI: 10.7150/ijbs.33773
|View full text |Cite
|
Sign up to set email alerts
|

P11 Loss-of-Function is Associated with Decreased Cell Proliferation and Neurobehavioral Disorders in Mice

Abstract: Although depression is associated with anxiety and memory deficit in humans, the molecular mechanisms of the complication remain largely unknown. In this study, we generated P11 knockout mice using CRISPR/Cas9 technology, as well as P11 knockout MEF cell lines, and confirmed depression-like phenotype. We observed that knockout of P11 in MEFs led to a decreased cell proliferation compared with P11 +/+ MEFs. Moreover, P11 knockout resulted in a larger cell size, which resulted probably from accumulated F-actin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The use of Cre-driver mouse lines for targeting local specific brain areas associated with depression and emotionality such as forebrain, hippocampus and VTA, provides a new approach to investigate proof of concept as to how the brain modulates mood and mood disorders [ 311 , 312 ]. Within the development of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-associated protein 9 (Cas9) system (CRISPR/Cas9) technology, the new generation of KO mice were developed in order to investigate the role of specific proteins on depression-like phenotype development and for further translation to clinical depression [ 313 , 314 , 315 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…The use of Cre-driver mouse lines for targeting local specific brain areas associated with depression and emotionality such as forebrain, hippocampus and VTA, provides a new approach to investigate proof of concept as to how the brain modulates mood and mood disorders [ 311 , 312 ]. Within the development of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-associated protein 9 (Cas9) system (CRISPR/Cas9) technology, the new generation of KO mice were developed in order to investigate the role of specific proteins on depression-like phenotype development and for further translation to clinical depression [ 313 , 314 , 315 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…A small receptor-binding protein p11 is a critical regulator of ChI activity within the NAc, as measured by the DA response to the mesolimbic DA reward stimulus pathway (Hanada et al, 2018 ; Liu et al, 2019 ). p11 is required for reward-mediated NAc ChI activation and the induction of acetylcholine (ACh) release, resulting in the enhancement of DA release (Hanada et al, 2018 ).…”
Section: Possible Influencing Factors That Mediate the Comorbidity Ofmentioning
confidence: 99%
“…Recent studies demonstrated that the methylations of some specific genes such as P11 ( 30 33 ), BDNF ( 34 38 ), SLC6A4 ( 39 42 ), and NR3C1 ( 43 45 ), were closely correlated to depression. For example, Svenningsson et al found that the P11 knockout mice showed anhedonia-like and despair-like behaviors assessed with above mentioned SCT, TST, and FST ( 33 ).…”
Section: Dna Methylation In Depressionmentioning
confidence: 99%